A note on optimal insurance in an information constrained federal economy with incomplete degree of enforceability and negotiation costs - Espino, Emilio (1999)
This paper studies the optimal insurance contract between a state and the central government in a federal economy with moral hazard, risk of repudiation (given some enforceability technology) and aggregate uncertainty. Also, it considers date 0 negotiation costs to implement this contract. The distribution of the fiscal resources locally collected by the province at t+1 are affected by period t state´s effort to collect taxes. Also, every period a state has the right to get a fixed proportion of the taxes nationally collected by the central government. These resources are identically and independently distributed across time. Using a recursive formulation of the allocation problem (following Atkeson (1991)), some basic properties of the optimal insurance contract are discussed showing when, in particular, it is actually optimal just to give up any attempt to provide insurance to the province.